Fungsi Ibu Muda Sebagai Orangtua Tunggal di Kota Batam - Yecy Artha Saragih; Emmy Solina; Rahma Syafitri (Social Issues Quarterly, 2023)
Young mothers as single parents are teenagers who have had children but their marriage relationship ended in divorce. Adolescents as single parents are fathers or mothers who will educate their children alone who are relatively young. However, in this study there are differences in adolescents as single parents in educating, protecting, giving a sense of security, as caregivers for their children. This study aims to determine how young mothers function as single parents in caring for and educating their children. This study uses a qualitative approach, the informants used in this study I got through random sampling. The data that was collected in this study used observation or observation techniques, interviews, documentation, books, journals and the internet. The results of this study found that the role of adolescents as mothers was eliminated because these adolescents did not fully carry out the functions and roles of mothers. however, the teenager actually gave his child to his parents (grandmother of toddlers) so that his parents would take care of and educate the child. Informants giving their children to their parents are also supported by the informant's parents, where the informant's parents say that they still give the informant a second chance for what happened to the informant, the informant's parents have also considered the informant's child as their child too., the informant's parents still love the informant so that the informant's parents who care for and protect children from informants.